SURVEI KEJADIAN PENYAKIT BUSUK PANGKAL BATANG (Phytophthora capsici) TANAMAN LADA (Piper nigrum. L) DI KABUPATEN KONAWE SELATAN - Asniah, Asniah; Syair, H; Wahyuni AS, Tuti (Jurnal Agroteknos, 2012)
The aim of this study was to know how big the rotten disease incidence on stalk base of pepper that was caused by Phytophthora capsici in South Konawe Regency and also to know what the farmer’s action to manage the rotten disease on stalk base of pepper. This study used survey and direct interview to the farmers. The average of rotten disease incidence on stalk base of pepper from six sampel Villages on the two Subdistrict in South Konawe Regency was 55,66 %, therefore this result include as the criteria of serious attack. The highest of disease event was found in Lamomea Village with the level of avarage attack was 83 %. Thus, this result was as of very serious attack. The highest disease incidence was found in Lamomea Village with the level of average attack was 83 %. Thus, this result was as very serious attack. The lowest disease event was found in Cialam Jaya Village with the level of average attack was 24 %, therefore this result classified as light attack. Keywords: disease incidence, rotton disease stalk base of pepper, Phytophthora capsici, survey